Knyha Psalmiv u novomu perekladi, psalmy 41-71 = The Book of Psalms in a New Ukrainian Translation, Psalms 41-71 - Colin, Dmytro (Bogoslovs'ki rozdymi, 2021)
The new translation of the Book of Psalms is part of a large project to translate the Holy Scriptures into Ukrainian, which has been underway since 2018. The project has already translated the New Testament (the edition is being prepared in 2022), poetic books of the Bible (in addition to the Psalms, the Book of Job, Proverbs, the Book of Ecclesiastes and the Song of Songs), translation of the Pentateuch and the Book of Prophet. The translation of the Psalms offered in Theological Reflections is the first publication of the above-mentioned translated books of Scripture.